Fairy garden handbook - Walsh, Liza Gardner (Down East, 2013)
Following up on her wildly popular Fairy House Handbook, author Liza Gardner Walsh encourages fairy-minded children to expand their outdoor activities to the garden. Sprinkled throughout with bits of fairy lore, this charming how-to includes basic information for beginning gardeners, then branches into appropriate categories for every fairy gardener.--COVER.